Avaliação do programa de medicina anti-estresse em mulheres com câncer de colo uterino submetidas à radioterapia - Ferreira, Ana Paula de Melo [UNESP] (2014)
The experience of onco-gynecological disease, provides distress, worries and losses in both patient and the family members, in particular, in that it has the responsibility of providing care. Clinically, there has been an attempt to modify the stress responses of individuals with anti-stress therapies, which focuses on the interactions between mind and body in the mental, social, spiritual and emotional factors directly affecting the health and capacity for self-care and self -awareness. The aim of this study was to evaluate the influence of the mindy-body medicine (MBM) in women with cervical cancer submitted to radiotherapy and their caregivers. The sample consisted of 60 women with cervical cancer submitted to radiotherapy, followed by Luxembourg Hospital in Belo Horizonte, Minas Gerais, and 60 caregivers were divided into two groups: case and control. The case group consisted of 30 women and their caregivers who participated of MBM. The control group did not participate in therapy (30 women and 30 caregivers). Participants completed a set of measurement instruments: the socio -demographic and clinical questionnaire, the questionnaire European Organization for Research and Treatment of Cancer Quality-of- Life Questionnaire (EORTC QLQ-C30), the Quality of Life Scale Caregiver / Family oncology and Distress Thermometer. A saliva sample for measurement of salivary cortisol before and after performing the techniques of MBM was collected. The groups were similar with respect to marital status, education, menopause, height and weight. The patients who participated MBM showed improved quality of life (p=0.0004), decreased distress (p>0.0001) and salivary cortisol (p>0.0001). The quality of life of caregivers of women with cervical cancer submitted to radiotherapy, which did not participate in MBM decreased (p=0.0475) compared to the group case. Caregivers PMAE participants showed decreased distress (p=0.0013) compared to the control group ...